New geothermal fluid flow simulation modified after Gwell Wellbore model using IAPWS industrial formulation 1997 for the thermodynamic properties of water and steam and incorporating the effect of NACL salt on viscosity and surface tension - Remoroza, Alvin I. (2007)
A computer program for geothermal wellbore simulation was developed using Visual Basic.Net programming language. It is a modified version of GWELL, a text-based multi-feedzone simulator that can handle CO2-H2O system. It incorporates inputs for mass fractions of CO2 and NaCl that both affect the thermodynamic properties of water and steam. The simulator is a tool to predict fluid properties of the flowing fluids along the length of the well and approximate contributions in a multi-feedzone well.